Factores de modelado que afectan la elección del teletrabajo y su impacto en la demanda en las redes de transporte - Vakilian, Rambod; Edrisi, Ali (Innovaciencia, 2019)
This research estimates the extent of using teleworking to mean the feasibility and appropriateness of this method of work for employees and professors according to their characteristics and features of career. The study population included university staff and professors in Tehran and data collection was carried out through 447 questionnaires. A logistic regression model was used to investigate the transport demand caused by teleworking. The results showed that various factors including history and percentage of telework and after that, the time delay of home-to-work and trave distance affected the model of transportation demand of professor’s members. For the staffing community, it had the greatest impact on teleworking, history and percentage of telework, followed by travel distances, latency from work to home, and latency from home to work.